2017
DOI: 10.4103/2249-4863.219988
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety and stress among school going adolescent in Chandigarh

Abstract: Context:Depressive disorders often start at a young age. There is a need for early identification of depression, anxiety, and stress (DAS) and prevention. The present study was undertaken to find the magnitude of DAS among adolescents.Aims:To find the mental health status of school going adolescents in Chandigarh. The objectives were (i) to study the prevalence of DAS among school going adolescents and (ii) to study the correlates of DAS.Settings and Design:A Cross-sectional survey of students of four classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 18 publications
3
45
4
Order By: Relevance
“…Almost majority of the studies in Indian and Asian setup had reported a significant association between socioeconomic status and depression. [41317293233] However, no such association has been found in our study. This could be explained by the fact that although socioeconomic status has a high impending impact on cognitive and behavioral domains of adolescents, the effect of this individual-level factor could be suboptimized or nullified by other predominant intervening factors such as parental education, occupation, and other basic background characteristics.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…Almost majority of the studies in Indian and Asian setup had reported a significant association between socioeconomic status and depression. [41317293233] However, no such association has been found in our study. This could be explained by the fact that although socioeconomic status has a high impending impact on cognitive and behavioral domains of adolescents, the effect of this individual-level factor could be suboptimized or nullified by other predominant intervening factors such as parental education, occupation, and other basic background characteristics.…”
Section: Discussioncontrasting
confidence: 58%
“…had found the combined prevalence of anxiety and depression to be about 57.65% among school-going adolescents. [4] Ganesh et al . had reported a much higher prevalence of 71.5%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations